Satellite Anomalies Benefits of a Centralized Anomaly Database and Methods for Securely Sharing Information Among Satellite Operators - Galvan, David A. (RAND Corporation, 2014)
Satellite anomalies are mission-degrading events that negatively affect on-orbit operational spacecraft. Maintaining a widely accessible and comprehensive database is one way to build an understanding of what situations are likely to result in satellite anomalies, but no such database exists. This report describes the nature and causes of satellite anomalies, and the potential benefits of a shared and centralized satellite anomaly database.